Perentjanaan "silt movement study" dengan perunut radioisotop Cr51 dipelabuhan Tg. Perak-Surabaja - Wijadi, Soetjipto (Pusat Penelitian Ps. Djum'at, 1972)
Study on silt movement using radioisotope Cr⁵¹ as radioactive stracer.